Konsepsi Pendidikan Kasih Sayang Dan Kontribusinya Terhadap Bangunan Psikologi Pendidikan Islam - Azam Syukur Rahmatullah (Universitas Alma Ata, 2014)
This article talking about love and affection education concepts is it has a great function in education world, is so great for student/pupils. With love and affection education will brings students/pupils to enjoyable in life, peaceful in heart, and have a certain attitude and all that from the heart. The aims application love and affection education is to clear juvenile delinquency.